1997
DOI: 10.1007/bf02459295
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility and reliability of predictions based on stochastic citation processes

Abstract: A statistical model for citation processes, a particular version of a non-homogeneous birth process, is analysed in the context of predictions of future citation rates, Important properties of the process were already studied by the author in earlier papers, Although the applicability of the model was demonstrated by several examples, practical aspects of predictions and questions of statistical reliability were not tackled so far. The present study is focused on the demonstration of the possibility of true pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…As such, we have not included any real data nor considered in detail the problems of data fitting. Some investigations along these lines have been given by Glänzel and Schoepflin (1994) and Glänzel (1997). Thus, at this stage the linear regression phenomenon as given by the second part of Theorem 3 must remain a conjecture, as must the less precise hypothesis that the regression function is increasing, and hence, a manifestation of success breeds success.…”
Section: Discussionmentioning
confidence: 95%
“…As such, we have not included any real data nor considered in detail the problems of data fitting. Some investigations along these lines have been given by Glänzel and Schoepflin (1994) and Glänzel (1997). Thus, at this stage the linear regression phenomenon as given by the second part of Theorem 3 must remain a conjecture, as must the less precise hypothesis that the regression function is increasing, and hence, a manifestation of success breeds success.…”
Section: Discussionmentioning
confidence: 95%
“…The slow ageing of social sciences literature would speak in favour of the choice of a longer windows [GLÄNZEL & SCHOEPFLIN, 1999], however the choice of three years still allows the evaluation of recent research results, on one hand, and this period is, at least at higher levels of aggregation, long enough to determine future citation impact, on the other hand [GLÄNZEL, 1997]. The three-year citation window has already successfully been applied in earlier studies (e.g., [GLÄNZEL, 1996]).…”
Section: Data Processingmentioning
confidence: 96%
“…DE SOLLA PRICE, 1965) and a number of studies now emerging demonstrate the significance of papers that have high initial citation rates (sometimes described as hot-topic or fast-breaking papers, see SMALL, 2004). There is also a significant body of relevant literature on citation-time distributions (OROMANER, 1983;GLÄNZEL & SCHOEPFLIN, 1995;EGGHE & RAO, 2001) and functions (GLÄNZEL, 1997;VLACHY, 1985 and references therein). OROMANER (1983) suggested that economics papers with the 'greatest repute' received the most citations during early and late periods after publication.…”
Section: Introductionmentioning
confidence: 95%